EH40/2002 Occupational exposure limits 2002 - supplement 2003 - UK. Health and Safety Executive (Sudbury, 2003)
It includes the new and amended exposure limits approved by HSC, and should therefore be read in conjunction with EH40/2002 Occupational Exposure Limits 2002, which remains current for another year. The key new information in the supplement includes: - three new MELs for substances for which Occupational Exposure Standards (OESs) were previously set: chloroethane, hydroquinone and manganese and its inorganic compounds; - amendment of the MELs for benzene and vinyl chloride; - withdrawal of 16 OESs: dichlorvos, divinylbenzene (mixed isomers), furfuryl alcohol (FA), glycerol trinitrate, nitrogen dioxide, nitrogen monoxide, sulphur dioxide, propylene dinitrate, ethylene dinitrate, subtilisins, sulphuric acid and five glycidyl ethers (2,3-epoxpropyl ethers). - no change to the OES for para-phenylenediamine, but an introduction of a skin notation for this substance; - narrowing the criteria applying to the OES for mineral oil mists in order to exclude metal working fluids. - three new biological monitoring guidance values for cyclohexanone, glycerol trinitrate and xylene.